2021
DOI: 10.3390/met11020234
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Behavior of Fe-Mn and Fe-Mn-Ag Powder Mixtures during Selective Laser Melting

Abstract: Additive manufacturing is a form of powder metallurgy, which means the properties of the initial metal powders (chemical composition, powder morphology and size) impact the final properties of the resulting parts. A complete characterization, including thermodynamic effects and the behavior of the metal powders at elevated temperatures, is crucial when planning the manufacturing process. The analysis of the Fe-Mn and Fe-Mn-Ag powder mixtures, made from pure elemental powders, shows a high susceptibility to sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Regarding the composition, the presence of Mn oxides is also usual. Kraner et al [112] reported that manganese is liable to oxidate during the atomization of the powders, so the oxygen is carried into the matrix, along with the Mn, forming Manganese oxides that do not dissolve into the matrix. In our case, the Aluminum, which comes from the impurities of the master alloys, just happens to replace de role of the Mn (Mn 2 O 3 ), leading to those mixed oxides of (Al,Mn) 2 O 3 type.…”
Section: As-built Microstructurementioning
confidence: 99%
“…Regarding the composition, the presence of Mn oxides is also usual. Kraner et al [112] reported that manganese is liable to oxidate during the atomization of the powders, so the oxygen is carried into the matrix, along with the Mn, forming Manganese oxides that do not dissolve into the matrix. In our case, the Aluminum, which comes from the impurities of the master alloys, just happens to replace de role of the Mn (Mn 2 O 3 ), leading to those mixed oxides of (Al,Mn) 2 O 3 type.…”
Section: As-built Microstructurementioning
confidence: 99%
“…The incorporation of the slag into AgCaLa is conclusive due to the lower surface tension and melting temperature of AgCaLa. Since the oxides of Mn decompose and melt at high temperatures, incorporation to FeMn with high melting temperature is less probable [46,110,111]. Additionally, the slag is located on the top of AgCaLa, and AgCaLa lies on FeMn; thus, the slag is in contact with AgCaLa and not with FeMn.…”
Section: Generation Of Slag and Chemical Composition Of Agcalamentioning
confidence: 99%
“…Powder-based metallurgical processes such as laser beam melting enable the processing of such materials, as mechanically mixed powders can be used [29,44,45]. Due to the small melt pool, strong melt flow, as well as rapid melting and solidification, homogenous and adaptable Ag phases in an iron-based matrix can be obtained via LBM [26,35,46,47]. Apart from the morphology of the Ag phases, the chemical composition has to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 60–64 ] Laser beam melting (LBM) is characterized by small melt pools with strong melt flow as well as rapid melting and solidification which enables the processing of such materials. [ 27,65–68 ] Following crucial aspects of the LBM process, on which the conducted research is based, are presented. The short exposure time to high temperatures during LBM is beneficial for the processing of degradable Ag alloys as the time for diffusion of alloying elements between both components is limited.…”
Section: Introductionmentioning
confidence: 99%